(untitled) (International journal of medical sciences, 2025)
Background: Dental implantation is a leading method for restoring dentition defects, but complications such as peri-implantitis and osseointegration failure remain significant challenges. Predicting these risks requires precise assessment of bone quality and microcirculation. Objective: To evaluate the role of modern diagnostic methods, specifically 3D radiography (CBCT) and Laser Doppler Flowmetry (LDF), in monitoring osseointegration and preventing complications during early functional loading of dental implants. Methods: A clinical study involving 90 patients (aged 25–61) with minor dentition defects was conducted. Patients were divided into three groups: Group 1 (n=28) received two-stage implantation with delayed loading; Group 2 (n=31) received implants with early functional loading (1 month post-surgery); Group 3 (n=38) received traditional bridge prostheses. Diagnostic monitoring included 3D CBCT for bone density and LDF for gingival microcirculation dynamics at 1, 3, 6, 9, and 12 months. Results: 3D radiography revealed that early functional loading (Group 2) stimulates bone density preservation comparable to the delayed loading group. LDF analysis showed that microcirculation in the peri-implant zone recovers faster under controlled early loading compared to traditional bridges, serving as a predictive marker for tissue stability. Conclusion: The combined use of 3D radiography and LDF allows for the objective prediction of complications by detecting early signs of bone loss and ischemia. These diagnostic tools are essential for determining the optimal timing for prosthetic loading and preventing implant failure.